Faktor-Faktor yang Berhubungan dengan Ibu Nifas dalam Mengkonsumsi Kapsul Vitamin A di UPTD Puskesmas Pengandonan Kecamatan Pengandonan Kabupaten OKU - Syarifah Herzaladini; Erma Puspita Sari; Siti Aisyah Hamid; Chairunnah Chairunnah (Universitas Batanghari Jambi, 2022)
Vitamin A has an important role for body functions, namely the function of vision, immunity, development and growth of the embryo. Vitamin A provides many benefits for postpartum mothers, namely increasing the production of breast milk (ASI). Postpartum mothers should take 2 capsules of Vitamin A because babies born have reserves. Giving 1 capsule of Vitamin A as much as 200,000 IU/Day to postpartum mothers to increase milk production for 60 days, while giving 2 capsules can increase the content of Vitamin A until the baby is 6 years old. month. The purpose of this study was to determine the relationship between factors that influence postpartum mothers in consuming vitamin A capsules in the UPTD Working Area of Pengandonan Health Center, Pengandonan District, Ogan Komering Ulu Regency in 2021.The research design used analytic with a cross sectional approach. The population in this study were postpartum mothers at the UPTD Puskesmas pengandonan in August 2021 with a total of 30 postpartum mothers. Collecting data using questionnaire data. Data analysis used univariate and bivariate analysis using chi square test. The results of the univariate analysis of 30 respondents who consumed vitamin A capsules were 21 respondents (70%), higher education was 22 respondents (73.3%), good knowledge was 21 respondents (70%), and positive attitude was 22 respondents (73). ,3%). Bivariate analysis showed that there was a relationship between education (0.001), knowledge (0.004) and attitude (0.019) with postpartum mothers' adherence to vitamin A capsule consumption at the UPTD Pengandonan Health Center, Pengandonan District, OKU Regency in 2021. The conclusion is that there is a relationship between education, knowledge and attitudes with postpartum mothers' adherence to vitamin A capsule consumption at the UPTD Pengandonan Health Center, Pengandonan District, OKU Regency in 2021. Suggestions for making comparisons and references in future research, for the UPTD of the Public Health Center for Information and Counseling for Postpartum Health, for postpartum mothers to access information about vitamin A and be more active in attending counseling activities.